Effects of the environmental enrichment on pigs’ behavior and performance - Rodrigo Fortunato de Oliveira; Rita da Trindade Ribeiro Nobre Soares; Rennan Herculano Rufino Moreira; Rayanne Prates de Andrade; Derek Andrew Rosenfield; Cristiane Schilbach Pizzutto (Revista Brasileira de Zootecnia, 2023)
ABSTRACT The study evaluates the influence of environmental enrichment on behavior, leucometry, and performance of commercial pigs. Thirty-two hybrid pigs (Landrace × Large White × Pietran), at 69 days of life, were divided into four groups and subjected to different environmental stimuli: concrete floor, with no enrichment (C); floor bedding with wood chips (CM); concrete floor, with mobiles (MO); floor bedding with wood chips and the presence of mobile (CM + MO). The study collected behavioral data of the animals during 84 days, through the growing and finishing phases, each lasting 42 days, assessing the animals’ position and behavior by the instantaneous scan sampling method. The animals received ad libitum water and a specially formulated feed following the nutritional requirements for growing and finishing phases. The study considered daily feed intake, daily weight gain, and feed conversion. Group CM in the growing phase showed prolonged standing position periods and demonstrated a greater exploration of their environment (2.1%). Groups MO and CM + MO, in the growing phase, demonstrated extended periods of interaction with the offered enrichments (10.8±2.1 and 9.1±2.8%, respectively). Piglets in the finishing phase housed in pens with floor bedding with wood chips and those housed in pens with floor bedding with wood chips and the presence of mobile (tires and chains) showed longer interaction time with enrichments (4.8 and 5.4%, respectively), compared with the other groups C and Mo. Group C remained overall the longest in a standing position in both breeding phases. There was no effect on the animals’ leukogram. Environmental enrichment with wood shavings (as beddings) and hanging mobiles improves behavioral aspects of piglets in the growing and finishing periods.